1989
DOI: 10.1093/bja/62.6.649
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioural Effects of Propofol on the Neonate Following Elective Caesarean Section

Abstract: Forty mothers undergoing elective Caesarean section under general anaesthesia were allocated randomly to receive either propofol 2.8 mg kg-1 (n = 20) or thiopentone 5 mg kg-1 (n = 20) for induction of anaesthesia. Twenty neonates delivered by uncomplicated vaginal delivery were evaluated also as unmedicated controls. Neurobehavioural examinations were carried out at 1, 4 and 24 h after delivery. Infants in the propofol group had lower Apgar scores at 1 and 5 min; 25% of them had muscular hypotonus at 5 min. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

1990
1990
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(24 citation statements)
references
References 16 publications
1
19
0
4
Order By: Relevance
“…23"24 Neurobehavioural assessment has been judged satisfactory after propofol (2.5 mg.kg-~) 27 although other workers have found lower scores after propofol (2.8 mg.kg -'l) than with thiopentone (5 mg. kg-~). 26 The NACS for the Chinese neonates in this study were less than those for non-Chinese. 12,27,28 All NACS were evaluated by the same paediatrician and were comparable with NACS 24 hr after normal vaginal deliveries and elective epidural Caesarean sections at this institution.…”
Section: Discussionmentioning
confidence: 50%
“…23"24 Neurobehavioural assessment has been judged satisfactory after propofol (2.5 mg.kg-~) 27 although other workers have found lower scores after propofol (2.8 mg.kg -'l) than with thiopentone (5 mg. kg-~). 26 The NACS for the Chinese neonates in this study were less than those for non-Chinese. 12,27,28 All NACS were evaluated by the same paediatrician and were comparable with NACS 24 hr after normal vaginal deliveries and elective epidural Caesarean sections at this institution.…”
Section: Discussionmentioning
confidence: 50%
“…There have been several studies comparing propofol to thiopental for induction of anaesthesia for elective Caesarean section [20][21][22][23][24][25][26][27][28][29][30]. These have showed little difference in neonatal Apgar scores or umbilical blood gas analysis.…”
Section: Resultsmentioning
confidence: 99%
“…These have showed little difference in neonatal Apgar scores or umbilical blood gas analysis. Two studies [21,22] observed signs of lighter anaesthesia in the propofol group; however out of 516 women randomly allocated to propofol or thiopental [20][21][22][23][24][25][26][27][28][29][30] there were two episodes of recall, both occurring with thiopental [20,27]. Three studies [24,27,29] suggested an improved maternal recovery with propofol while four [20][21][22]30] found no difference.…”
Section: Resultsmentioning
confidence: 99%
“…43 Indeed one authority questions its use for routine Caesarean delivery. 44 In spite of this, we believe it to be a suitable induction agent in the pregnant patient with AIP.…”
Section: Anaesthetic Considerationsmentioning
confidence: 93%